Striving for Zero: Reducing Healthcare-Associated Infections (HAI) - A Target, Vision, or Philosophy - Prof Jaffar Al-Tawfiq (International Journal of Infectious Diseases)
Introduction: Healthcare-associated infections (HAIs), which include both conventional and non-traditional types, continue to pose a serious threat in contemporary healthcare environments. Examining the current state of HAIs, preventative measures, and the idea of ''zero HAI'' as a goal and a philosophy are the objectives of this study. Methods: Data on HAI prevalence, types, prevention techniques, and the development of the ''zero HAI'' concept were analyzed in a thorough literature review. Case studies of HAI outbreaks and their effects on healthcare environments were also looked at in the study. Results: Traditional HAIs, such as CLABSI, CAUTI, VAE, and SSI, remain a significant concern. SSIs account for 290,485 infections annually and have the highest mean hospital cost per infection at $25,546. Non-traditional HAIs, such as MERS-CoV outbreaks, significantly impact healthcare practices, with surgical mask usage increasing from 2,947.4 to 10,284 per 1,000 patient-days during outbreaks. Since its introduction in 2000, the ''zero HAI'' concept has grown to become a key component of infection prevention initiatives. Discussion: The philosophy of “zero” infection has resulted in significant drops in infection rates, even though reaching absolute zero HAIs is still difficult. Studies emphasize the significance of all-encompassing infection prevention techniques, such as environmental cleaning, staff education, and hand hygiene. The necessity for flexible preventive measures is highlighted by the way that newly emerging infectious diseases exacerbate established HAIs. Conclusion: Despite its ambitious nature, the goal of achieving zero HAIs is a strong incentive for ongoing advancements in infection prevention and control. Healthcare facilities should recognize the challenges of reaching absolute zero infections and work toward meaningful reductions in HAI rates through all-encompassing, evidence-based strategies.